PENGARUH PROMOSI JABATAN TERHADAP MOTIVASI KERJA PEGAWAI - Berian Hariadi (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2020)
Job promotion allows agencies to make the most of employees' skills and abilities. Job promotions are often given to reward employees who perform very well. Employees who are valued for promotion will be motivated to give even higher performance if they feel that effective performance leads to promotion. This study aims to see how much influence the promotion of position on employee work motivation and how strong the relationship promotion position on employee work motivation. The results of the research aimed at work motivation and promotion have a linear and strong relationship, the promotion of position will be able to increase employee motivation. Keywords: Job Promotion, Work Motivation